Women's attitudes towards a human papillomavirus-based cervical cancer screening strategy: a systematic review. Issue 4 (5th August 2022) - Nothacker, Julia; Nury, Edris; Roebl Mathieu, Marianne; Raatz, Heike; Meerpohl, Joerg J; Schmucker, Christine
Abstract : Objective: To provide insights into women's attitudes towards a human papillomavirus (HPV)-based cervical cancer screening strategy. Data sources: Medline, Web of Science Core Collection, Cochrane Library, PsycINFO, CINAHL and ClinicalTrials.gov were systematically searched for published and ongoing studies (last search conducted in August 2021). Methods of study selection: The search identified 3162 references. Qualitative and quantitative studies dealing with women's attitudes towards, and acceptance of, an HPV-based cervical cancer screening strategy in Western healthcare systems were included. For data analysis, thematic analysis was used and synthesised findings were presented descriptively. Tabulation, integration, and results: Twelve studies (including 9928 women) from USA, Canada, UK and Australia met the inclusion criteria. Women's attitudes towards HPV-based screening strategies were mainly affected by the understanding of (i) the personal risk of an HPV infection, (ii) the implication of a positive finding and (iii) the overall screening purpose. Women who considered their personal risk of HPV to be low and women who feared negative implications of a positive finding were more likely to express negative attitudes, whereas positive attitudes were particularly expressed by women understanding the screening purpose. Overall acceptance of an HPV-based screening strategy ranged between 13% and 84%. Conclusion: This systematic review provides insights into the attitudes towards HPV-based cervical cancer screening and its acceptability based on studies conducted with women from USA, Canada, UK and Australia. This knowledge is essential for the development of education and information strategies to support the implementation of HPV-based cervical cancer screening. Systematic review registration: PROSPERO (CRD42020178957).